IDNLearn.com provides a platform for sharing and gaining valuable knowledge. Ask your questions and receive detailed and reliable answers from our experienced and knowledgeable community members.

Find an equation for the line that passes through the points [tex](2, -6)[/tex] and [tex](-4, -4)[/tex].

Sagot :

Sure! To find the equation of the line passing through the two given points, [tex]\((2,-6)\)[/tex] and [tex]\((-4,-4)\)[/tex], let's follow these steps:

1. Calculate the slope ([tex]\(m\)[/tex]) of the line:
The slope of a line passing through two points [tex]\((x_1, y_1)\)[/tex] and [tex]\((x_2, y_2)\)[/tex] is given by the formula:
[tex]\[ m = \frac{y_2 - y_1}{x_2 - x_1} \][/tex]

For the points [tex]\((2, -6)\)[/tex] and [tex]\((-4, -4)\)[/tex]:
[tex]\[ m = \frac{-4 - (-6)}{-4 - 2} = \frac{-4 + 6}{-4 - 2} = \frac{2}{-6} = -\frac{1}{3} \][/tex]

So, the slope [tex]\(m\)[/tex] is [tex]\(-\frac{1}{3}\)[/tex].

2. Find the y-intercept ([tex]\(b\)[/tex]) of the line:
Using the slope-intercept form of the equation of a line, which is [tex]\(y = mx + b\)[/tex], we need to solve for [tex]\(b\)[/tex]. We can use one of the given points to do this. Let's use the point [tex]\((2, -6)\)[/tex].

Substitute [tex]\(m = -\frac{1}{3}\)[/tex], [tex]\(x = 2\)[/tex], and [tex]\(y = -6\)[/tex] into the equation [tex]\(y = mx + b\)[/tex]:
[tex]\[ -6 = -\frac{1}{3}(2) + b \][/tex]

Simplify and solve for [tex]\(b\)[/tex]:
[tex]\[ -6 = -\frac{2}{3} + b \][/tex]

To isolate [tex]\(b\)[/tex], add [tex]\(\frac{2}{3}\)[/tex] to both sides:
[tex]\[ -6 + \frac{2}{3} = b \][/tex]

Convert [tex]\(-6\)[/tex] to a fraction with a common denominator:
[tex]\[ -6 = -\frac{18}{3} \][/tex]

Thus:
[tex]\[ -\frac{18}{3} + \frac{2}{3} = b \][/tex]
[tex]\[ b = -\frac{16}{3} \][/tex]

So, the y-intercept [tex]\(b\)[/tex] is [tex]\(-\frac{16}{3}\)[/tex].

3. Write the equation of the line:
Now that we have the slope [tex]\(m = -\frac{1}{3}\)[/tex] and the y-intercept [tex]\(b = -\frac{16}{3}\)[/tex], we can write the equation of the line in slope-intercept form:
[tex]\[ y = -\frac{1}{3}x - \frac{16}{3} \][/tex]

Therefore, the equation of the line that passes through the points [tex]\((2, -6)\)[/tex] and [tex]\((-4, -4)\)[/tex] is:
[tex]\[ y = -\frac{1}{3}x - \frac{16}{3} \][/tex]